Cognitive disorders of patients with cerebrovascular disorders who suffered from COVID-19 - Mischenko Vladyslav; Dmytriieva Olena; Zdesenko Iryna; Lehka Mariia (Psychiatry, Neurology and Medical Psychology, 2023)
The purpose of the research was to study the features of cognitive functions in COVID-19 patients with chronic cerebrovascular disorders. It has been discovered, that by all patients, who have recovered from COVID-19, moderate and severe cognitive impairments were identified. In this group of patients a significant progression of cognitive deficit was noted in compared to the group of patients without COVID-19. The main forms of disorders in COVID-19 patients with cerebrovascular pathology, were violations of attention and decreasing of information processing speed, and disorders of short-term working memory, instead long-term memory and recognition memory suffered much less. Our research demonstrated better sensitivity of the MoCA scale for detecting cognitive impairment in COVID-19 patients with cerebrovascular pathology. The majority of patients had cognitive impairment within 6 months after recovery from COVID-19, what indicated the necessity for long-term monitoring and timely treatment of these patients.